Utility of 16-MDCT angiography for comprehensive preoperative vascular evaluation of laparoscopic renal donors - Steven S. Raman (2018)
OBJECTIVE. Our objective was to determine the efficacy of 16-MDCT angiography in preoperative evaluation of vascular anatomy of laparoscopic renal donors. METHODS AND MATERIALS. Fifty-five consecutive renal donors (25 men and 30 women) underwent 16-MDCT angiography followed by donor nephrectomy. In the arterial and nephrographic phases, images were acquired with 60% overlap and 0.6-mm reconstruction in both phases after 120 mL of iohexol was injected at 4 mL/sec. On a 3D workstation, images were evaluated retrospectively by two abdominal imagers blinded to surgical results with respect to number and branching pattern of renal arteries and major and minor renal veins. These CT angiography results were compared with surgical findings. RESULTS. The surgically confirmed sensitivity of both reviewers (1 and 2) using the MDCT data for detection of renal arteries was 98.5% (65 of 66), and accuracies were 97.0% for reviewer 1 and 95.5% for reviewer 2. Sensitivity and accuracy detection of renal veins was 97% (61 of 63) and 98% (62 of 63) for reviewer 1 and reviewer 2, respectively. Sensitivity and accuracy detection of early arterial bifurcation (< 2 cm from aorta) was 100% (14 of 14), and sensitivity in detection of late venous confluence (< 1.5 cm from aorta) was 100% (8 of 8). All major renal venous variants were identified; reviewer 1 identified 78% (18 of 23) minor venous variants, and reviewer 2 identified 83% (19 of 23) minor venous variants. There were no hemorrhagic complications at surgery. Excellent agreement between reviewers (kappa = 0.92-0.97) was achieved for detection of normal and variant anatomy. CONCLUSION. 16-MDCT angiography enabled excellent preoperative detection of arterial anatomy and venous laparoscopic donor nephrectomy. © American Roentgen Ray Society.